Design and Optimization of Thioglycosyl–naphthalimides as Efficient Inhibitors Against Human O-GlcNAcase - Shen, Shengqiang; Dong, Lili; Chen, Wei; Wu, Renjie; Lu, Huizhe; Yang, Qing; Zhang, Jianjun (Frontiers in Chemistry, 2019)
β-N-acetylhexosaminidases represent an important class of exoglycosidases and have emerged as the promising targets for drug and pesticide discovery. Among these, human O-GlcNAcase (hOGA) has been reported to be closely linked to several diseases such as Alzheimer’s disease, diabetes, and cancer. Potent hOGA inhibitors with high selectivity are therefore of great significance for the regulation of the corresponding physiological processes. In this study, several classes of novel and readily available thioglycosyl-naphthalimides bearing the amide linker were designed and synthesized. To investigate their potency and selectivity, the inhibitory efficiencies towards hOGA and human β-N-acetylhexosaminidase B (HsHexB) were assayed. Especially, compounds 10a (Ki = 0.61 μM) and 16l (Ki = 0.72 μM) exhibited excellent inhibitory potency against hOGA and high selectivity (HsHexB, Ki > 100 μM). In addition, during the preparation of these thioglycosyl−naphthalimides, a new practical method was developed for the synthesis of ureido glycosides from trichloroethyl carbamates at room temperature and normal pressure without catalyst. Furthermore, the possible binding modes of hOGA with 10a, 10d, and 16j were studied using molecular docking and molecular dynamics simulations to explore the molecular basis for the potency of these thioglycosides. This work present here provides useful clues for the further structural optimization towards hOGA.